Characterization of escherichia coli isolated from aquacultural environment - Sheila Maria, Andrew Stanley (Universiti Malaysia Sarawak (UNIMAS), 2011)
Aquaculture environment is often exposed to contamination from the sewage and organic pollutants which are the main habitat for E. coli. Pathogenic E. coli can cause severe disease outbreaks through food consumption from aquaculture sources. Currently, antibiotics are used in the aquaculture industries for treatment of diseases among aquatic organisms, as a growth promoter, water treatment and pollution control. Nineteen E. coli isolates from the aquaculture environment were tested for their antibiotic resistance by disc diffusion method. The plasmid DNA extraction of the isolates was performed by alkaline lysis method. The genetic variations among the isolates were analysed by (GTG)5 PCR. Based on antibiotic susceptibility test, 100% of the isolates were resistant towards erythromycin while the lowest level of resistance was against chloramphenicol and tetracycline (31.58%). Plasmid analysis revealed that 63.16% isolates contain plasmid DNA, whereas 36.84% are plasmidless. (GTG)5 PCR analysis indicated that E. coli isolated were grouped into 2 main clusters and 6 minor clusters. This study proved that E. coli isolates from the aquaculture environment were highly diverse, as shown by their differences in antibiotic resistance patterns, plasmid profiles and (GTG)5 PCR analysis. The multiple antibiotic resistance of the isolates indicates the potential hazard associated with antibiotic resistance bacteria from the aquaculture environment.